INTERTEKSTUALITAS DAN KRITIK SOSIAL DALAM CERPEN DODOLITDODOLITDODOLIBRET: MEMBACA ULANG SENO GUMIRA AJIDARMA DI ERA DIGITAL - Gumarpi Rahis Pasaribu (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2025)
This study aims to analyze the forms of intertextuality and social criticism in the short story Dodolitdodolitdodolibret by Seno Gumira Ajidarma, as well as their relevance to the conditions of freedom of expression in the digital era. This study uses a descriptive qualitative approach with Julia Kristeva's intertextuality theory and Pierre Bourdieu's social criticism theory. The primary data is the short story text, while secondary data comes from literature studies and previous studies. The results show that Seno Gumira Ajidarma builds intertextuality through the use of sound, repetition, and absurdity as symbolic forms of censored communication. Social criticism appears in the form of satire against the power that silences freedom of speech. When reread in the context of the digital era, the message in this short story remains relevant, because it shows the existence of a form of